A Study of FNAC of Cervical Lymph Nodes - Shakya, G; Malla, S; Shakya, KN; Shrestha, R (Journal of Nepal Health Research Council, 2009)
Background: Fine Needle Aspiration Cytology (FNAC) is a reliable and least expensive method suitable for developing countries like Nepal for the investigation of lymphadenopathy. Knowledge about the pattern of lymphadenopathy is useful in pathological reporting as well as in many clinical settings with diagnostic dilemma. This is a baseline study to investigate the pattern of cervical lymphadenopathy by lymph node FNAC in Nepalese population. Methods: A retrospective study was conducted by critically analyzing the case reports on cervical lymph node FNAC from three years’ records (July 2005 to June 2008) at the National Public Health Laboratory, Teku, Kathmandu. Review of all cytological reports were done according to standard guidelines and the diagnosis was classified and correlated with patients’ age and ethnicity to explore the pattern and association. Results: Of 508 cervical lymph node FNAC cases, 50.4% was reactive non-specific, 22.4% was tubercular, 4.8 % malignant, 10% chronic granulomatous and the remaining was acute suppurative (12.4%). Highest incidence of malignancy was seen in the fifth decade (50%). Whereas, tubercular lymphadenopathy was found with increasing frequency through childhood (10.5%) and adolescence (21.7%) to young adulthood (30.4%), probably indicative of waning immunity of BCG vaccination. Ethnic groups comprising of Tamang, Sherpa and Bhote had the highest incidence of malignant as well as tubercular lymphadenopathy. Conclusion: The relationship of malignant and tubercular lymphadenopthy with age and ethnicity deserves further study. Efforts at preventing tubercular and early diagnosing malignant lymphadenopathy and reducing morbidity in general will find great usefulness in such associations. Key words: Cervical Lymphadenopathy, Fine Needle Aspiration Cytology, Pattern DOI: 10.3126/jnhrc.v7i1.2267 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 1-5